2021
DOI: 10.1681/asn.2020111664
|View full text |Cite
|
Sign up to set email alerts
|

Roxadustat for Renal Anemia in ESRD from PKD Patients: Is It Safe Enough?

Abstract: Akizawa et al. 1 report roxadustat's noninferiority to darbepoetin alfa in treating hemodialysis-dependent CKD anemia in their phase 3 study. However, in this trial, we could not find the exact data of the primary disease of CKD or the proportion that polycystic kidney disease (PKD) 1-4 accounts for. PKD is the fourth leading cause of ESKD in adults worldwide; however, in a phase 2 trial of roxadustat in CKD-associated anemia in Japanese patients, the ratio of polycystic kidney disease was 6.3% (five in 80). 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…This contrasts to the response to the exogenous ESAs with supraphysiological dosing and high EPO concentrations [ 40 ]. More effectively than exogenous ESAs, the HIF stabilizers also improve iron status and transferrin saturation by inhibition of hepcidin, thus leading to increased intestinal iron absorption and better utilization of iron stores in the body [ 43 ]. In contrast to short-term studies [ 7 ], long-term treatment with roxadustat also shows that an iron supplement should be administered [ 10 ].…”
Section: Clinical Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts to the response to the exogenous ESAs with supraphysiological dosing and high EPO concentrations [ 40 ]. More effectively than exogenous ESAs, the HIF stabilizers also improve iron status and transferrin saturation by inhibition of hepcidin, thus leading to increased intestinal iron absorption and better utilization of iron stores in the body [ 43 ]. In contrast to short-term studies [ 7 ], long-term treatment with roxadustat also shows that an iron supplement should be administered [ 10 ].…”
Section: Clinical Efficacymentioning
confidence: 99%
“…Compared with exogenous ESA, roxadustat was associated with more frequent adverse events such as vomiting (RR 1.30, 95% CI 1.02–1.65), headache (RR 1.27, 95% CI 1.05–1.53), and thrombosis (RR 1.31, 95% CI 1.05–1.63) [ 10 ]. Roxadustat might unfavorably lead to the growth of renal cysts in autosomal dominant polycystic kidney disease (ADPKD) because the HIF pathway appears to be involved in cyst progression [ 43 ]. Roxadustat led to reduced thyroid-stimulating hormone levels in a multimorbid hemodialysis patient, but, to date, mechanism and clinical implications are unclear [ 33 ].…”
Section: Clinical Toxicitiesmentioning
confidence: 99%
“…Eleftheriadis et al (2021) supposed that roxadustat might affect the adaptive immune system and increase urinary tract infection and pneumonia incidence. While Liu et al (2021) indicated that long-term use of roxadustat may lead to the progression of renal cysts and cause adverse events of infection. More studies are needed to confirm that roxadustat predisposes patients to infection or that these results are merely statistical differences.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some evidence that roxadustat can cause a variety of side effects, mainly diarrhea, vomiting, peripheral edema, headache, back pain, fatigue, and hyperkalemia ( Akizawa et al, 2020c ; Liu et al, 2020 ). In addition, HIF functions in the progression of polycystic kidney disease (PKD), and roxadustat may promote the growth of renal cysts ( Liu et al, 2021 ). A case report found that roxadustat reduced the TSH levels in hemodialysis patients, but the mechanism and clinical significance of this effect is unclear ( Tokuyama et al, 2021 ).…”
Section: Effect Of Roxadustat On Anemiamentioning
confidence: 99%